Main Pancreatic Duct Dilatation: a Sign of High Risk for Pancreatic Cancer - Tanaka, Sachiko; Nakaizumi, Akihiko; Ioka, Tatsuya; Oshikawa, Osamu; Uehara, Hiroyuki; Nakao, Miho; Yamamoto, Kiyomi; Ishikawa, Osamu; Ohigashi, Hiroaki; Kitamra, Tsugio (Japanese journal of clinical oncology, 2002)
Background: The prognosis of pancreatic ductal adenocarcinoma remains very poor, but is better in patients with a small tumor without local infiltration. The identification of the sign of high risk for pancreatic cancer will lead to early detection and improvement of the prognosis of this disease. The purpose of this study was to evaluate the main pancreatic duct dilatation as a sign of high risk for pancreatic cancer. Methods: The diameter of the main pancreatic duct was measured by ultrasonography. The proportion of cases with main pancreatic duct dilatation was retrospectively examined in a pre-cancer group (39 subjects in whom pancreatic cancer developed more than 1 year later and surgically resected) and in a control group (10 244 subjects). Then the proportions in both groups were compared using the odds ratio. Results: The proportion of cases with a slight dilatation (≥2 mm in diameter) of the main pancreatic duct was 65% in the pre-cancer group, more than 4 years before the resection of the pancreatic cancer. In contrast, it was 5.35% in the age-matched control subjects. The odds ratio of 32.5 (95% confidence interval: 10.9–107.3) shows a significant association between the main pancreatic duct dilatation and the pre-cancer condition. Moreover, the proportion and the mean diameter of the dilated duct in the pre-cancer group increased with time. Conclusion: Slight dilatation of the main pancreatic duct appears to be a sign of high risk for pancreatic cancer. The systematic examination of high-risk subjects is recommended for the early detection of pancreatic cancer.